Total phenolic content and scavenging activity of water and methanol extracts from the stems of Mas Cotek (Ficus deltoidea var angustifolia) / Imanuel Bin Justine - Justine, Imanuel (Faculty of Applied Sciences, 2008)
This study investigates the total phenolic content and scavenging activity of the water and methanol extracts of the stems of Mas Cotek (Ficus deltoidea var angustifolia). The Folin-Ciocalteu reagent was used in determining the total phenolic content. The water extract showed a higher value of total phenolic content (350 mg/g) compared to the methanol extract (135 mg/g). The scavenging activity was measured using the 1,1- diphenyl-2-picrylhydrazyl (DPPH) methods. The water extract showed 59.64 % scavenging effect while 44.90 % for methanol extract at concentration of 2500 and 6250 ppm, respectively. As a conclusion, the water extracts from the stems of Mas Cotek (Ficus deltoidea var angustifolia) has greater scavenging activity than the methanol extract. Both water and methanol extracts showed lower value than the standard quacertin. This indicate that the scavenging potential for both extracts were not as effective as in quacertin. Further work need to be done in order to assess the full antioxidant potential toward the stems of the plant.